MATRIKs METALOPROTEINASE-2 DI METASTASIS KARSINOMA PAYUDARA (Matrix Metalloproteinase-2 In Breast Cancer Metastastis) - Besse Rosmiati; Uleng Bahrun; Ruland DN Pakasi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Matrix Metalloproteinase-2 is a family of extra cellular matrix degrading proteinases. Study results on the role of MMP-2 in breastcancer progression and metastasis are still controversial. The aim of this study was to know the MMP-2 level by analyzing in metastaticand non metastatic breast cancer patients by using a cross sectional design, it was carried out in the Wahidin Sudirohusodo, Ibnu Sina,Labuang Baji Hospitals and at the Research Unit of UNHAS Makassar from April 2012 until June 2012. The 56 breast cancer patientswere divided into two groups: metastatic and non metastatic based on their thorax photo, ultrasonography and/or bone scan results. Theywere also divided into early and advanced stage, based on their TNM staging. The matrix metalloproteinase-2 level was determined byELISA method. The result of this study showed that the mean levels of MMP-2 in metastatic and non metastatic breast cancer were 20.18ng/mL and 17.14 ng/mL, respectively. The independent sample T test showed there was a significant difference (p=0.018) in MMP-2levels between metastatic and non metastatic breast cancer. The mean level of MMP-2 in early and advanced stages was 17.10 ng/mLand 18.31 ng/mL, respectively, the independent sample T test showed no significant difference of MMP-2 level between both stages. Oneway ANOVA test showed no significant difference of MMP-2 level based on tumour size and regional lymph node infiltration. The MMP-2contributed to the metastasis in breast cancer patients. The matrix metalloproteinase-2 level in metastatic was higher than in the nonmetastatic breast cancer, so this condition could be used as a biomarker to predict the metastasis of breast cancer.